Vulvovaginitis: epidemiological aspects - Duarte, Geraldo; Landers, Daniel Vicente (Brazilian Journal of Sexually Transmitted Diseases, 1998)
This artic le describes the epidemiologic aspects of vulvovaginitis on an evolulionary and care perspective, pointing out the most important e tiologic groups of this disease. One of its focus is on the negative iníluence from the disagreement of definition , terminology and etiology ofvulvovaginitis on its epidemiological evaluation , and lhe necessity LO establish a consensus about these questions. The most frequent causes of vulvovaginitis are bacterial vaginosis, candidiasis and trichomonia s is, highligthing the ir frequency, predisposition and recutent factors. The other causes of vulvovaginitis are also very important and we sugges t incorporating, in a definitive way. ali of them in the differential diagnosis of the causes of vulvovaginitis.